Identifying the true European ‘low-cost airports' - Jimenez Perez, Edgar; Suau-Sanchez, Pere (Universidade da Beira Interior, 2019)
This paper discusses the long-term effects of low-cost carrier (LCC) presence at European airports and identifies the airports that have benefited the most from LCC consolidation during the current century. The research uses ‘LCC Market Share’, in terms of seats, to measure the relative importance of LCCs within each airport; and introduces ‘EU LCA Rank’ as a normalised metric of the capacity share of every airport in the European low-cost segment. It evaluates the trends between 2001 and 2018 in a sample of the 300 largest European airports, by total seats in 2018, using OAG supply information (seats by carrier). Results highlight the role that LCCs have played in boosting the growth of airports, both primary and secondary, that were keen to appreciate the development of the low-cost segment earlier. Indeed, despite the fact that LCCs have put many airports on the European map, during the second half of the period of analysis growth has been more significant for major airports. In that sense, this paper contributes a better understanding of the recent dynamics in European LCCs choice of airports and, in particular, the long-term effects that this disruptive business model have had for airports.
Keywords: Low cost airport; Low cost carrier; Longitudinal analysis; European airports